Structural Changes in the Renminbi Exchange Rate Mechanism. Issue 2 (25th April 2021) - Su, Guanyu; Qian, Junhui
Abstract: This paper examines structural changes in China's exchange rate mechanism. For this purpose, we propose a predictive model incorporating three factors that influence the central parity rate: a smoothing factor, a market factor, and a basket factor. We first apply the model to analyze the effects of 12 exchange rate reforms since 2005, treating these reforms as predetermined structural breaks. Among other results, we find that the main impact of introducing a "counter‐cyclical factor" is to weaken the role of the basket factor. We estimate structural breaks in data, assuming that the number and dates of breaks are unknown, and we find that, although the majority of estimated breaks occur within the neighborhood of exchange rate reforms, there are breaks due to other external shocks such as the escalation of the China–US trade conflict in May 2019. It is suggested that our model may be used to guide future currency reforms in China.